Equal Distribution of National Income through the Concept of Green Economy: an Exploratory Studies - Syah, Ardy Firman (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2023)
The initiation of national economic growth gives the government a focus on handling economy equally in both rural and urban areas. The considerations that make the economy must be sustainable among others which the current generation who enjoys goods and services produced from natural resources and the environment has a moral obligation to leave the services of these natural resources for future generations. The aim of this research is initiated to promote equitable economic growth through the conservation of natural resources that can be used sustainably from each generation. The approach used in this research is qualitative with exploratory study method. The analysis technique used is literature search and case analysis related to the entity of equal distribution of national income and the green economy concept. The results of this study indicate that there are seven strategic steps and green economy using macro-regional economic indicators namely genuine saving to monitoring the distribution of national income. This result is to describe concepts of green economy, green growth and green development are basically intended to operationalize the linkages of economic, social and environmental pillars in the context of sustainable development.